Familial aggregation of schizotypy in schizophrenia-spectrum disorders and its relation to clinical and neurodevelopmental characteristics. (January 2017) - Soler, J.; Ferentinos, P.; Prats, C.; Miret, S.; Giralt, M.; Peralta, V.; Fañanás, L.; Fatjó-Vilas, M.
Abstract: Introduction: This study explored schizotypy as a familial liability marker for schizophrenia-spectrum disorders (SSD) by examining: 1) the aggregation of schizotypy in families with a SSD patient, 2) whether familial resemblance of schizotypy is associated with ridge dissociations (RD), another SSD liability marker, 3) whether schizotypy aggregation patterns influence patients' psychopathology. Methods: The sample comprised 30 SSD patients and 82 healthy first-degree relatives. Schizotypy was assessed using the Structured Interview for Schizotypy-Revised (SIS-R). Patients' psychopathology was evaluated using the Comprehensive Assessment of Symptoms and History (CASH). RD were identified as anomalies of the dermal ridge junction. Familiality of SIS-R was investigated using a linear mixed model (LMM) and its strength was assessed using an intraclass correlation coefficient (ICC). Another LMM using the absolute differences in SIS-R scores between all possible pairs of relatives as the dependent variable was fitted to obtain an intra-family resemblance score, a family-specific indicator of resemblance of SIS-R scores within each family. Results: 1) Schizotypy was familial (ICC = 0.30); families with high resemblance displayed low schizotypy, whereas families with low resemblance included at least one healthy relative with high schizotypy (p < 0.001). 2) Relatives with RD had higher SIS-R scores (p = 0.018) and belonged to families with discordant schizotypy scores among members (p < 0.001). 3) Patients from high schizotypy families showed more severe disorganized symptoms at the psychotic episode (p = 0.035) and 1 year later (p = 0.011). Conclusions: Schizotypy is a marker of vulnerability for SSD that runs within a subgroup of families. The schizotypy familial aggregation pattern correlates with RD in relatives and with patients' psychopathology. Graphical abstract: